2009
DOI: 10.1080/18811248.2007.9711556
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Core Physics Experiments on Fresh and Irradiated BR3 MOX Fuel in REBUS Program

Abstract: As part of an international experimental program REBUS, core physics experiments have been implemented on a UO 2 core, which consists of 3.3 and 4.0 wt% UO 2 fuel rods in a square pitch of 1.26 cm, and two partial MOX cores, which replace 7 Â 7 UO 2 fuel rods in the center of the UO 2 core by fuel bundles made of fresh BR3 MOX fuel or irradiated BR3 MOX fuel with an average burnup of 20 GWd/t. Burnup calculations of the BR3 MOX fuel were performed using a general-purpose neutronic calculation code SRAC, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Neutronics analysis of the data have been reported by the organizations participating in the programs. 1,[3][4][5][6][7][8][9][10] Alander et al 6) and Yamamoto et al, 7) who analyzed the measured isotopic compositions of the high-burnup BWR MOX fuel in the REBUS program, observed that the burnup calculations based on an infinite assembly model overestimated fissile isotopes of U and Pu. They attributed it to harder neutron energy spectra in the assembly calculations than those under actual irradiation conditions, where the MOX assembly was burnt surrounded by UO 2 assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Neutronics analysis of the data have been reported by the organizations participating in the programs. 1,[3][4][5][6][7][8][9][10] Alander et al 6) and Yamamoto et al, 7) who analyzed the measured isotopic compositions of the high-burnup BWR MOX fuel in the REBUS program, observed that the burnup calculations based on an infinite assembly model overestimated fissile isotopes of U and Pu. They attributed it to harder neutron energy spectra in the assembly calculations than those under actual irradiation conditions, where the MOX assembly was burnt surrounded by UO 2 assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…[6] and has been confirmed to be relatively reliable except for some nuclides though the comparison with isotopic inventories measured by different organizations in some of international programs. The measured inventories provided the burnup of the measured fuel sample by applying Neodymium-148 Method [12].…”
Section: Comparison Between Calculated and Measured Inventoriesmentioning
confidence: 99%
“…The core characteristics of the irradiated MOX core are summarized in Table 4. Table 4 also shows those of the fresh MOX core (hereafter, referred to as 'fresh BR3 MOX core'), where a 7 6 7 test bundle consisting of 24 fresh BR3 MOX rods was loaded [6]. Since the core loaded with a fresh MOX bundle consisting of fresh MOX rods of 5.52 wt% (Pu-fissile) corresponding to the 9 6 9 MOX assembly were not performed, we used the core characteristics of the fresh BR3 MOX core as a substitute to evaluate burnup reactivity as mentioned in Section 4.3.…”
Section: Critical Experiments On Irradiated Mox Fuelmentioning
confidence: 99%
See 1 more Smart Citation
“…The underestimation of the diffusion calculations with the SRAC code has been reported for some critical experiment analyses. 9,10) The diffusion coefficient determination method using the present method will be improved in the next step. P1 transport calculations were more accurate than P0 transport calculations; 2D transport calculations with axial buckling correction were sufficiently accurate as well.…”
Section: Comparison Of Analysis Modelsmentioning
confidence: 99%